Development of an Assessment Rubric for Story Writing Skills in Indonesian Integrated with Acehnese Folklore for Senior High School - Verawati; Lustyantie, Ninuk; Murtadho, Fathiaty (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to develop an assessment rubric for storytelling skills in Indonesian that is integrated with Acehnese folklore, specifically for high school students (SMA). The development of this rubric is based on the need for a valid, reliable, and contextual assessment tool to measure students' creative writing abilities while utilizing local cultural values. The research method used is the Research and Development (R&D) model, which includes stages of design, validation by language and cultural experts, limited trials, and rubric revisions. The rubric instrument integrates linguistic aspects, story text structure, and distinctive elements of Acehnese folklore as learning materials that encourage creativity and cultural understanding. The validation results show that the rubric has a high content validity and can be used as a guide for objective and comprehensive storytelling assessment. The implementation of the rubric in high school classes also demonstrated an improvement in the quality of students' written work and a deeper cultural awareness. This study concludes that the developed rubric effectively supports storytelling learning based on local wisdom, while also enriching students' language and cultural competencies.